Development of disaster nursing education and training programs in the past 20 years (2000–2019): A systematic review. (April 2021) - Loke, Alice Yuen; Guo, Chunlan; Molassiotis, Alex
Abstract: Background: Nurses play a pivotal role in disaster management across the globe. With the call for all nurses to be prepared for disasters, disaster nursing education and training programs have expanded globally. However, a clear picture of the development and coverage of disaster nursing education and training programs is lacking. Objectives: This study aimed to establish an overall picture of the development of disaster nursing education and training programs in the last 20 years, outline the contents included, approaches adopted and outcomes reported. Methods: A systematic search for relevant literature published between January 2000 to December 2019 was conducted using electronic databases including the CINAHL, MEDLINE, PubMed, Web of Science, and Scopus with the keywords on disaster nursing education and training. Findings. A total of 75 eligible studies were identified from 3395 potentially relevant articles. The numbers of disaster nursing education and training programs increased gradually over the past 20 years. They were offered in various countries with an unbalanced geographical distribution. Most of the existing programs focused on disaster preparedness and response, especially on the skills of triage during disaster response, instead of addressing the full spectrum of disaster management that included mitigation, preparedness, response, and recovery phases. Multiple approaches and technologies were adopted, including competency-based, all-hazard, inter-professional, flipped classroom, simulation, tabletop exercises, and virtual reality ones. Nearly half of the included programs adopted a pre- and post-test evaluation to examine the outcomes of learning and all of the programs reported significant increases in nursing professionals' knowledge and skills of related content on disaster management covered in the training programs. Conclusions: This review provides nurse leaders, educators and researchers in nursing with an understanding of the state-of-art of the existing disaster nursing education and training programs. More disaster nursing research are necessary to enhance the knowledge, skills and readiness of the nursing professionals for disaster management in meeting global disaster challenges.